Pressure Work and Viscous Dissipation Effects on Heat Transfer in a Parallel–Plate Microchannel Gas Flow. (April 2019) - Ramadan, K. M.
ABSTRACT: Convective heat transfer in a parallel plate microchannel gas flow is investigated analytically and numerically, considering the effects of viscous dissipation, pressure work, shear work, axial conduction and rarefaction. Analysis is performed with constant wall temperature and constant wall heat flux boundary conditions for both gas cooling and heating. The results presented demonstrate the significance of the combined effect of pressure work and viscous dissipation, shear work, rarefaction degree and axial conduction on microchannel convective heat transfer, in both the thermally developing and fully developed flow regions. Viscous dissipation and pressure work in a pressure-driven microchannel gas flow are of comparable magnitudes and may not be neglected from the energy equation. The shear work at the wall, which is effectively the combined effect of viscous dissipation and pressure work, needs to be included in the Nusselt number for better predictions of heat transfer.